2024
DOI: 10.3390/membranes14010023
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Cation Exchange Membranes: A Review

Stef Depuydt,
Bart Van der Bruggen

Abstract: Cation exchange membranes (CEMs) play a significant role in the transition to a more sustainable/green society. They are important components for applications such as water electrolysis, artificial photosynthesis, electrodialysis and fuel cells. Their synthesis, however, is far from being sustainable, affecting safety, health and the environment. This review discusses and evaluates the possibilities of synthesizing CEMs that are more sustainable and green. First, the concepts of green and sustainable chemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 153 publications
0
2
0
Order By: Relevance
“…Specifically, as GC/GC–MS techniques are routinely used in QC for solvent analysis, we opted to use GC–MS to complement our LC-HRMS results. As from a sustainability standpoint the use of NMP is not tenable and should be phased out, we focused on GC–MS evaluation of NBP, which is deemed as one of the next-generation green solvents , and has shown great promise as a solvent for sustainable peptide synthesis. ,,,,,,,, To this end, the three NBP batches were evaluated by GC–MS, and in these analyses, these samples exhibited higher purities (97.79–99.98%, Figure a) than purities observed in the corresponding LC-HRMS analyses (94.18–99.76%, Figure ). Nevertheless, while the higher GC–MS purities indicated that some of the impurities observed by LC-HRMS were either not resolved and/or degraded during the conditions of the analysis, we did observe a back-eluting NBS impurity (Figure b), which was present to a similar extent (n.d.1.97%, Figure a) to which NBP-OOH was observed by LC-HRMS (n.d.2.20%, Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, as GC/GC–MS techniques are routinely used in QC for solvent analysis, we opted to use GC–MS to complement our LC-HRMS results. As from a sustainability standpoint the use of NMP is not tenable and should be phased out, we focused on GC–MS evaluation of NBP, which is deemed as one of the next-generation green solvents , and has shown great promise as a solvent for sustainable peptide synthesis. ,,,,,,,, To this end, the three NBP batches were evaluated by GC–MS, and in these analyses, these samples exhibited higher purities (97.79–99.98%, Figure a) than purities observed in the corresponding LC-HRMS analyses (94.18–99.76%, Figure ). Nevertheless, while the higher GC–MS purities indicated that some of the impurities observed by LC-HRMS were either not resolved and/or degraded during the conditions of the analysis, we did observe a back-eluting NBS impurity (Figure b), which was present to a similar extent (n.d.1.97%, Figure a) to which NBP-OOH was observed by LC-HRMS (n.d.2.20%, Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The main drawbacks are its high methanol permeability [6,9,10] and high production cost [9][10][11][12]. In addition, it contributes to global PFAS pollution, endangering human health and the environment [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%